Integritas Tablet Ekstrak Daun Sirsak dengan Crospovidone - Handayani, Fajar; Kurniasari, Devita; Indrati, Oktavia; Perdana Kusuma, Aris (Universitas Islam Indonesia, 2025)
Background: Annona muricata L. (A. muricata) leaf contains several active compounds, including flavonoids, which are known to have antioxidant properties. People only use A. muricata leaves as antioxidants by boiling them in water. Therefore, the development of tablet potential is necessary to enhance user comfort and storage stability.Objective: The aim of this research was to determine the disintegration time of A. muricata leaf extract tablets with varying levels of the disintegrating agent crospovidone and to determine the best disintegrating level according to the results of evaluating the physical properties of the tablets.Methods: Tablets are made using the wet granulation method with a composition of 2-5% crospovidone. The resulting granules are tested for water content, flow time, angle of repose, and tapping. The resulting tablets were tested for hardness, friability, and disintegration time.Results: The test results show that crospovidone and lactose can produce excellent A. muricata leaf extract tablets.Conclusion: Crospovidone 3.5% produces optimum A. muricata leaf extract tablets with a friability of 0.36% and a disintegration time of 7.82 minutes.